Measuring Share-Based Payments to Customers - Afterman, Allan B (Accounting & Auditing Update Service, 2019)
INTRODUCTION The Financial Accounting Standards Board (FASB) has issued Proposed Accounting Standards Update (ASU) No. 2019-400, Compensation-Stock Compensation (Topic 718) and Revenue from Contracts with Customers (Topic 606): Codification Improvements- Share-Based Consideration Payable to a Customer, to provide guidance on measuring share-based payments made to a customer. In June 2018, the FASB issued ASU No. 2018-07, Compensation-Stock Compensation (718): Improvements to Nonemployee ShareBased Payment Accounting, which amended the FASB Accounting Standards Codification (ASC or the "Codification") by expanding the scope of FASB ASC Topic 718, Compensation-Stock Compensation, to include share-based payment transactions for acquiring goods and services from non-employees (and, thus, superseded the guidance in FASB ASC Subtopic 505-50, Equity- Equity-Based Payments to Non-Employees). FASB ASC 718 * FASB ASC 718-10-15, Compensation-Stock Compensation-Overall-Scope and Scope Exceptions, would be amended to (1) cover share-based payment transactions in which a grantor acquires goods or services to be used or consumed in the grantor's own operations or provides consideration payable to a customer, and (2) require that the transaction price (and, thus, revenue) be reduced by the share-based consideration payable to a customer in accordance with FASB ASC 606-10-32, unless the consideration is for the purchase of a distinct good or service from the customer, in which case the purchase would be accounted for in the same manner as the entity accounts for other purchases. * FASB ASC 718-10-35, Compensation-Stock Compensation-Overall-Subsequent Measurement, would be amended to clarify that classification and subsequent measurement of the award would be subject to FASB ASC 718, unless the share-based payment award is subsequently modified and the grantee is no longer a customer.